Impact behavior of model porous concretes - Agar Ozbek, Ayda Safak; Weerheijm, J.; Breugel, K. (Springer Science and Business Media LLC, 2019)
In this work, findings of a numerical study performed to investigate the impact behavior of porous concrete, modeled as a four phase cementitious composite consisting of aggregates, cement paste, interfacial transition zones (ITZ) and air, are presented. The numerical analyses contributed to the process of designing a special type of concrete for safety purposes i.e. as a protective building material to be used in safety walls outside important buildings or munition magazines for storing explosives. In case of an explosion, large concrete fragments that are formed, cause a very important threat. Therefore, in the scope of a research project, designing a special type of concrete having sufficient strength, but fracturing into small fragments under impact loading was aimed. In the numerical analyses, model porous concretes, in which the amounts and properties of pores and aggregates could be varied individually, were used to see the sole effect of each parameter. According to the results, it was found that at constant total porosity, the impact strength increased with decreasing pore size while multiple fragmentation was observed. On the other hand, the impact strengths of porous concretes with different size aggregates (with constant total aggregate content and porosity) were approximately the same when no ITZ was defined. However, when ITZ was present, the impact strength was found to decrease as the aggregates were finer. This trend was also valid for the respective full concretes. Representative experimental results of porous concretes were also presented in order to support the numerical results.
Keywords: Porous concrete; Aggregates; Finite element method; Finite element analysis; Concrete aggregates; Explosions; Total aggregates; Cementitious composites; Impact strength; Explicit; Impact; Multiple fragmentations; Interfacial transition zone; Concretes; Pore size; Numerical results; Porous concretes; Numerical analysis